We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
973
1
avatar+1016 

 

Enter your answer, in simplest radical form, in the box.

 Dec 26, 2017

Best Answer 

 #1
avatar
+3

Simplify the following:
3 sqrt(-50)

Express sqrt(-50) in terms of i.
sqrt(-50) = sqrt(-1) sqrt(50) = i sqrt(50):
3 i sqrt(50)

Simplify radicals.
sqrt(50) = sqrt(2×5^2) = 5 sqrt(2):
3 i×5 sqrt(2)

Multiply 3 and 5 together.
3×5 = 15:
15i sqrt(2)

 

 Dec 26, 2017
 #1
avatar
+3
Best Answer

Simplify the following:
3 sqrt(-50)

Express sqrt(-50) in terms of i.
sqrt(-50) = sqrt(-1) sqrt(50) = i sqrt(50):
3 i sqrt(50)

Simplify radicals.
sqrt(50) = sqrt(2×5^2) = 5 sqrt(2):
3 i×5 sqrt(2)

Multiply 3 and 5 together.
3×5 = 15:
15i sqrt(2)

 

Guest Dec 26, 2017

27 Online Users

avatar
avatar